Formulation, Characterization and In-Vitro Evaluation of Dasatinib Loaded Solid Lipid Nanoparticles for Oral Delivery - Mohamed Yasir Arafath (Journal of Global Pharma Technology, 2019)
Objective: Dasatinib (DST) is a BCS Class II drug having very low solubility and high permeability. The absolute bioavailability of DST is about 14 to 34% due to an extensive first-pass effect. For improving the bioavailability of DST, solid lipid nanoparticles (SLNs) were developed using triglycerides (trimyristin, tripalmitin, and tristearin). Methods: Hot homogenization followed by ultrasonication method was used to prepare DST-SLNs. The prepared SLNs were characterized for particle size, Poly dispersity index (PDI), Zeta potential (ZP), Entrapment efficiency (EE) and Drug Content. Invitro release studies using dialysis bag method in 0.1N Hcl and pH 6.8 Phosphate buffer were conducted. Results: DST-SLNs prepared with Dynasan-118(E4) having the size of 150.73nm, PDI of 0.20, ZP of -29.1 mV with 93.56% of EE were optimized. In addition, long-term physical stability of the optimized SLNs was investigated at refrigerated and room temperature for 180days and it was stable for long period. FTIR and DSC studies revealed that no interaction between the drug and lipids. Scanning electron microscopic studies showed nearly spherical shape particles with increased polydispersity index. Formulation containing Dynasan-118(E4) showed highest percentage drug release among all the prepared SLNs. Release of drug from DST-SLNs (F4, S4, and E4) followed Higuchi, the best fit with the highest correlation coefficients were shown in Higuchi plot. The mechanism of release is by diffusion controlled as indicated by R2 value of Higuchi and n value of Korsemeyer-Peppas equation. Conclusion: Dasatinib loaded solid lipid nanoparticles is a good drug delivery system with desirable release characteristics.